Neo-Kantianisme dan Implikasinya untuk Penelitian Terhadap Agama - Sermada Kelen Donatus (Studia Philosophica et Theologica, 2021)
The elaboration of the theme done by the author aims at introducing the philosophical stream of Neo-Kantianism based on Kant’s epistemology and at pointing out the implication of Neo-Kantianism on the scientific research about religion. This purpose should be realized by describing the main philosophical concept of Neo-Kantianism within its two wellknown schools. Its implication on the religion can be explained. The critique on religion can be pointed out, the theology of pluralism can be compared with the catholic theology, and the divine revelation provided by Neo-Kantianism can be enlighted under the scrutiny of rationality. The outcome of the research is lying on the recognition and the acceptance of the adherents’ Neo Kantianism to the theology as a scientific discipline based on the divine revelation under the authority of the human rationality. The conclusion taken out from the research is that the philosophy of Neo-Kantianism has given strong impact on the scientific research about religion. The divine revelation should be enlightened by the various scientific approaches before it is reflected theologically.